UNLOCKING COMPREHENSION: PREVIEWING STRATEGY FOR EFFECTIVE READING (Web of Teachers: Inderscience Research, 2025)
Reading comprehension is a crucial skill that supports academic success and lifelong learning. However, many students struggle to understand and retain what they read. One effective method to enhance comprehension is the previewing strategy, which encourages readers to engage with the text before reading it in detail. This article explores the role and objective of previewing in effective reading, examines its benefits, and provides practical methods for implementation in the classroom.